ESTUDO DA BIOATIVIDADE E AÇÃO ANTIBACTERIANA DE VITROCERÂMICAS OBTIDAS POR CRISTALIZAÇÃO CONTROLADA. - SILVA, Gleison Lopes da (2020)
This work aimed to study bioactivity and antibacterial activity of glass-ceramics obtained by controlled crystallization as a function of time in the glass system 59,5B2O3-2P2O5-9,5CaO- 19,5Na2O-9CaF2-0,5Ag2O (% in mol). The glassy samples were prepared by melt-quench method, cut into slices and subsequently treated with constant temperature (530 ° C), varying the heat treatment time: 0, 4, 8, 12, 24 and 36 hours. DTA results prove changes in the glass structure, due to the decrease in Tx values and thermal stability. X-ray diffraction measurements of the samples before heat treatment revealed broad bands at 29 ° and 46 ° (2θ), associated with borate glasses. Heat-treated samples have characteristic peaks of crystalline phases developed during the heat treatment (CaNa3B5O10, Ca3(PO4)2, Na2B8O13 e Ag0 ). It was observed that the longer heat treatment time, the greater crystallite size for the Ag0 and Ca3(PO4)2 phases, and the greater percentage of crystallization of the glass-ceramics. FTIR results presented changes in the borate glass network, resulting from the controlled crystallization process. Bioactivity in vitro of the materials was analyzed by immersion in simulated body fluid (SBF) for 7, 14, 21 and 28 days. XRD diffractograms revealed precipitation of Hydroxyapatite and AgCl in the samples during immersion in SBF. FTIR spectra showed bands characteristic of Hydroxyapatite. pH measurements revealed a higher ion exchange rate among the crystallized samples, being associated with microstructural changes on surface during heat treatment that changing e reactivity of the glass ceramics and phase solubility. The results obtained reveal that the glass-ceramics present a bioactive behavior when immersed in SBF, possessing bone bonding capacity, by forming Hydroxyapatite on its surface. Even after 28 days of immersion, metallic silver was detected in the samples for 12 h, 24 h and 36 h, which indicates the stability in physiological fluid of this crystalline phase and the potential long-term antibacterial behavior of the samples. Antibacterial activity test against E.colli 6305 bacteria showed inhibition halos with similar lengths between samples treated by : 0 h (17 mm), 12 h (17 mm) and 36 h (18 mm), indicating that controlled crystallization did not inhibit the release of Ag+ ions. Therefore, studied glass-ceramics have the potential to be used as biomaterials, in bone treatments, and to inhibit any bacterial infections.